PERKEMBANGAN SENJATA NUKLIR SEBAGAI SUATU ISU KEAMANAN, SARANA DIPLOMASI DAN SENJATA PEMUSNAH MASSAL - Nelda Zahra Amany; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The issue of nuclear weapons has become an issue that is often discussed in international dialogues and forums. The presence of nuclear weapons cannot be separated from its development in three ways, namely as a security issue, a means of diplomacy and as a weapon of mass destruction. The purpose of this research is to determine the development of nuclear weapons as a security problem in the international world. Furthermore, the type of research used in this research is qualitative with secondary data and using data collection techniques sourced from books, documents, journals, websites and thesis related to this research. The results obtained from this study indicate that the role of nuclear weapons is divided into three, namely as a security issue, a means of diplomacy and weapons of mass destruction. This is demonstrated by nuclear weapons which often cause security dilemmas, their emergence as a part of weapons of mass destruction, and cause many countries to carry out defense by forming international cooperation. Keywords: Diplomacy, nuclear weapons, security, weapons of mass destruction